2016
DOI: 10.1007/s12031-016-0760-5
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol Treatment in Familial Dysautonomia: Open-Label Pilot Study

Abstract: Familial dysautonomia (FD) is an autosomal recessive congenital neuropathy, primarily presented in Ashkenazi Jews. The most common mutation in FD patients results from a single base pair substitution of an intronic splice site in the IKBKAP gene which disrupts normal mRNA splicing and leads to tissue-specific reduction of IKBKAP protein (IKAP). To date, treatment of FD patients remains preventative, symptomatic and supportive. Based on previous in vitro evidence that tocotrienols, members of the vitamin E fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This study demonstrated that tocotrienol mediated: 1) reduction in the number of pneumonias; 2) reduced sweating, blotching and dizziness; and 3) increased stability in walking. 76 After 3 months of the tocotrienol therapy, a significant increase in the expression of the exon 20-containing ELP1 transcript was detected in peripheral blood cells of these patients. For reasons that are unclear, no increase in the exon 20-containing ELP1 transcript in the peripheral blood cells was detected at the 6-month time point.…”
Section: Treating Fd: the In Vivo Response To Gene-targeting Therapiementioning
confidence: 86%
See 3 more Smart Citations
“…This study demonstrated that tocotrienol mediated: 1) reduction in the number of pneumonias; 2) reduced sweating, blotching and dizziness; and 3) increased stability in walking. 76 After 3 months of the tocotrienol therapy, a significant increase in the expression of the exon 20-containing ELP1 transcript was detected in peripheral blood cells of these patients. For reasons that are unclear, no increase in the exon 20-containing ELP1 transcript in the peripheral blood cells was detected at the 6-month time point.…”
Section: Treating Fd: the In Vivo Response To Gene-targeting Therapiementioning
confidence: 86%
“…The tocotrienol-mediated reduction in the frequency of pneumonias 76 and hypertensive crises, 73 which are the leading causes of death in FD patients, 14 , 77 strongly support their continued administration. The tocotrienol-mediated increased tear production 73 – 75 has helped FD patients avoid the recurrent corneal abrasions/ulcers that typically result from the lack of tear production.…”
Section: Treating Fd: the In Vivo Response To Gene-targeting Therapiementioning
confidence: 87%
See 2 more Smart Citations
“…Although its efficacy in FD remains controversial (Lee et al, 2009), its anticancer properties have been in part related to proteasome inhibition (Chen et al, 2011;Modernelli et al, 2015). Therefore, a rational approach to reduce carfilzomib toxicity while maintaining splicing profile improvement and proteasome blocking could be to combine this drug with EGCG or with tocotrienols, members of the vitamin E family, that have been shown to upregulate IKBKAP transcription and to provide clinical benefit to FD patients (Anderson et al, 2003b;Cheishvili et al, 2016).…”
Section: Discussionmentioning
confidence: 99%